Business communication (BMS 1st year 1st semester) - Choudhury Nina Roy, Nambiar Lekha (Vipul prakashan,Mumbai, 2008)
B.M.S.
ENGLISH
Keywords: Business communication (BMS 1st year 1st semester); B.M.S.; B.M.S.